2018
DOI: 10.3324/haematol.2018.188219
|View full text |Cite
|
Sign up to set email alerts
|

N-linked glycosylation modulates the immunogenicity of recombinant human factor VIII in hemophilia A mice

Abstract: Immune responses to factor VIII remain the greatest complication in the treatment of severe hemophilia A. Recent epidemiological evidence has highlighted that recombinant factor VIII produced in baby hamster kidney cells is more immunogenic than factor VIII produced in Chinese hamster ovary cells. Glycosylation differences have been hypothesized to influence the immunogenicity of these synthetic concentrates. In two hemophilia A mouse models, baby hamster kidney cell-derived factor VIII elicited a stronger imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 53 publications
(55 reference statements)
2
39
0
Order By: Relevance
“…As recently reported, rh coagulation factor (rhF) VIII expressed in BHK cells is more immunogenic than that produced in CHO cells (Lai et al, 2018). As recently reported, rh coagulation factor (rhF) VIII expressed in BHK cells is more immunogenic than that produced in CHO cells (Lai et al, 2018).…”
Section: Product Glycosylationmentioning
confidence: 82%
“…As recently reported, rh coagulation factor (rhF) VIII expressed in BHK cells is more immunogenic than that produced in CHO cells (Lai et al, 2018). As recently reported, rh coagulation factor (rhF) VIII expressed in BHK cells is more immunogenic than that produced in CHO cells (Lai et al, 2018).…”
Section: Product Glycosylationmentioning
confidence: 82%
“…On the other hand, glycans may be protective, acting to shield underlying FVIII epitopes. The presence of glycans shields overlying FVIII protein epitopes and incomplete glycan coverage of the FVIII protein is hypothesised to result in antibody complexes and enhanced immunogenicity (Lai et al , ,b). Although there is a lack of evidence suggesting which hypothesis is more clinically relevant, a recent study proposes that glycans primarily drive the differences in immunogenicity between pdFVIII and rFVIII products even in the presence of its chaperone von Willebrand Factor (VWF) (Jankowski et al , ).…”
Section: Factor VIII Proteinmentioning
confidence: 99%
“…Recently, it was demonstrated that opsonisation via complement protein C3 plays an important role in enhancing the efficiency of FVIII uptake and the subsequent development of an immune response (Rayes et al , ). Alternatively, antibody‐mediated opsonisation of FVIII via immunoglobulin (Ig)‐M has been observed to increase inhibitor development (Lai et al , ,b), potentially acting through a complement receptor 1‐ or 2‐dependent process (Ferguson et al , ). The binding of IgG to FVIII similarly enhances its uptake but through Fcγ receptor mechanisms (Pincetic et al , ).…”
Section: Cellular Perspectives Of the Factor VIII Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Potential reasons for differences in immunogenicity of FVIII produced by varying cell types need to be better addressed. Interestingly, FVIII produced in cultured cells with different N‐glycosylation showed differences in inhibitor formation in haemophilic mice, albeit no human data have yet been published on this issue . Von Willebrand Factor (vWF), which binds to FVIII and is critical for its half‐life in the circulation, has been shown in several studies to affect FVIII immunogenicity, possibly by changing APC and/or endothelial cell FVIII uptake .…”
Section: Introductionmentioning
confidence: 99%